Association of serum ferritin with metabolic syndrome in eight cities in China. Issue 3 (3rd February 2020) - Wang, Meichen; Zhao, Ai; Szeto, Ignatius Man‐Yau; Wu, Wei; Ren, Zhongxia; Li, Ting; Feng, Haotian; Wang, Peiyu; Wang, Yan; Zhang, Yumei
Abstract: Objective: This study aims to evaluate the cross‐sectional association of serum ferritin (SF) and the risk of metabolic syndrome (MetS) and its components among adults in eight cities in China. Methods: Subjects were recruited using a combination of systematic cluster random sampling and purposive sampling in eight cities in China. The sociodemographic characteristics, data of lifestyle factors, self‐reported disease history, and 24‐hr dietary intake were obtained using a validated questionnaire. Anthropometry was performed, and fasting blood was collected to test the SF, fasting blood glucose (FBG), insulin, high‐sensitivity C‐reactive protein (hs‐CRP), triglycerides (TG), and cholesterols. Logistic and linear regression analyses were conducted to investigate the associations, adjusting for age, city level, smoking, drinking, weekly moderate‐to‐vigorous activity, dietary factors, hs‐CRP, and BMI. Results: Serum ferritin level is positively correlated with total cholesterol, TG, FBG, HOMA‐IR, and hs‐CRP after adjusting for age and BMI. The odds ratio (OR) for MetS in the highest quartile of SF was 2.23 (1.32, 3.77) after adjusting for men, compared with the lowest quartile. An elevated ferritin concentration was significantly related to hypertriglyceridemia ( p < .001) and elevated glucose ( p = .013) among men, but not among women. Furthermore, compared with Q1, the OR for insulin resistance in the ferritin Q4 group was 3.08 (1.50, 6.32) among men and 1.96 (1.19, 3.24) among women. Conclusion: A positive association between elevated SF and MetS and its components including hypertriglyceridemia and elevated glucose was found in multivariate analyses among men, and SF levels are independently associated with IR. Abstract : We aim to assess the associations between serum ferritin and components of the metabolic syndrome (and analyses are stratified by gender). The study population was randomly selected based on place of residence, including eight cities in China. In total, 1, 659 subjects were included.